Pelatihan Penulisan Bahan Ajar Seni Rupa Lokal Bagi Guru Seni Budaya Sekolah Menengah Pertama - Tangsi Tangsi; Sofyan Salam; Alimuddin Caco (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The Community Partnership Program (PKM) activity aims to increase the awareness and ability of Junior High School Cultural Arts teachers in writing local art teaching materials that will be taught in Arts and Culture subjects. The trainees were 11 Junior High School Arts and Culture teachers. The training was held for two days face-to-face with material on how to write teaching materials, criteria for evaluating materials, and using pictures / illustrations in teaching materials. Guiding participants in writing teaching material is done remotely by utilizing information communication technology. During the training the participants were very enthusiastic about participating in the activity, both face-to-face and remote guidance. From this training produced local art teaching materials for junior high schools. Local art teaching materials produced are Ceramic Art, Songkok Guru, and Karaeng Laikang Traditional House. The teaching material contains a description of local fine arts along with related images. Supporting factors for the training in writing teaching materials, namely: (1) the availability of local art works in each region, (2) there is no material about local art that is ready to be taught in schools, and (3) support for technological advances. The obstacles in writing teaching materials are the low awareness of teachers to write and the lack of leadership appreciation for writing teaching materials.